To history of origin of copyright on literature works - Pylypchuk, O. O. (History of science and technology, 2016)
The article is devoted to the history and development of the institution of copyright in literary works. Highlights the main stages of formation of copyright in Europe in the XV-XIX centuries. Traced the process of formation the national legal base on intellectual property under the laws of the Russian Empire in the late XIX – early XX centuries.